Programming Google App Engine with Java - Sanderson, Dan (Sebastopol, CA O'Reilly, 2015)
How to build highly scalable Java applications in the cloud with Google App Engine for intermediate and advanced web and mobile app developers
Introducing Google App Engine -- Creating an application -- Configuring an application -- Request handlers and instances -- Using modules -- Datastore entities -- Datastore queries -- Datastore transactions -- Datastore administration -- The Java Persistence API -- Using Google Clud SQL with App Engine -- The memory cache -- Fetching URLs and web resources -- Sending and receiving email messages -- Sending and receiving Instant Messages with XMPP -- Task queues and scheduled tasks -- Optimizing service calls -- Managing request logs -- Deploying and managing applications -- Index
Includes index
1
Keywords: Google Apps; Application software -- Development; Java (Computer program language); Web site development -- Computer programs